2021
DOI: 10.1038/s41598-021-88704-8
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origin of the crayfish plague pathogen, Aphanomyces astaci, to the Southeastern United States

Abstract: The oomycete Aphanomyces astaci is an emerging infectious pathogen affecting freshwater crayfish worldwide and is responsible for one of the most severe wildlife pandemics ever reported. The pathogen has caused mass mortalities of freshwater crayfish species in Europe and Asia, and threatens other susceptible species in Madagascar, Oceania and South America. The pathogen naturally coexists with some North American crayfish species that are its chronic carriers. Presumptions that A. astaci originated in North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 80 publications
2
28
0
Order By: Relevance
“…We also determined that the A. astaci found in this P. clarkii population belongs to the D-haplogroup. Four haplotypes have been identified for A. astaci in P. clarkii: d1, d2, d3, and usa6 (Makkonen et al, 2018;Martín-Torrijos et al, 2018, 2021b. The four mitochondrial rnnS sequences obtained in this study are all identical to those corresponding to either the d1 or d2 rnnS haplotypes reported by Makkonen et al (2018).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We also determined that the A. astaci found in this P. clarkii population belongs to the D-haplogroup. Four haplotypes have been identified for A. astaci in P. clarkii: d1, d2, d3, and usa6 (Makkonen et al, 2018;Martín-Torrijos et al, 2018, 2021b. The four mitochondrial rnnS sequences obtained in this study are all identical to those corresponding to either the d1 or d2 rnnS haplotypes reported by Makkonen et al (2018).…”
Section: Discussionsupporting
confidence: 61%
“…In Costa Rica, although there are no native crayfish species, there are approximately 26 native species of freshwater decapods (21 shrimp species belonging to the families Atyidae and Palaemonidae, and 15 crab species belonging to Pseudothelphusidae) (Lara and Wehrtmann, 2011;Lara et al, 2013;Magalhães et al, 2015). Despite the seemingly narrow host range of A. astaci (Unestam, 1972;Diéguez-Uribeondo et al, 2009), several studies have shown transmission of the pathogen to other freshwater decapods including Atya gabonensis, Atyopsis moluccensis, Eriocheir sinensis, Macrobrachium dayanum, Macrobrachium lanchesteri, Neocaridina davidi, Palaemon kadiakensis, and Potamon potamios (Schrimpf et al, 2014;Svoboda et al, 2014;Putra et al, 2018;Mrugała et al, 2019;Martín-Torrijos et al, 2021b). Although the coexistence of native freshwater decapods with P. clarkii has not been reported yet in Costa Rica, the potential impact of the invasive species presence on freshwater fauna in the country should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular typing by the random amplified polymorphic DNA (RAPD) of A. astaci axenic laboratory cultures (Huang et al, 1994) has allowed the identification of five distinct genotype groups, labeled alphabetically from A to E (reviewed in Rezinciuc et al, 2015). The application of genotyping markers to clinical samples (i.e., DNA isolates from infected crayfish), particularly the analysis of microsatellite loci (Grandjean et al, 2014) and sequencing of mitochondrial ribosomal genes (Makkonen et al, 2018), allowed the discovery of additional variation among A. astaci strains, both in outbreaks of the disease (Grandjean et al, 2014;Martín-Torrijos et al, 2018) and from non-symptomatic hosts (Mrugała et al, 2017a;Martín-Torrijos et al, 2018;Panteleit et al, 2019;Martín-Torrijos et al, 2021). However, the vast majority of crayfish plague outbreaks in Europe analyzed so far have been linked to one of the four RAPD-defined genotype groups either isolated from one of the widespread crayfish invaders (groups B, D, E; Huang et al, 1994;Diéguez-Uribeondo et al, 1995;Kozubíková et al, 2011b) or associated with historical mortalities (group A; Huang et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, causative agents of crayfish plague outbreaks have been genotyped in regions where crayfish plague is considered a major threat to indigenous crayfish conservation, and thus research has been intensive in the past two decades. It is important to keep in mind that the diversity of A. astaci in its native range is largely unexplored, and substantial additional variation has been already discovered since this oomycete became studied in other natural hosts (Panteleit et al, 2019;Martín-Torrijos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%